2020
DOI: 10.34117/bjdv6n3-098
|View full text |Cite
|
Sign up to set email alerts
|

Produtos alternativos para o manejo de doenças em frutos de mamoeiro pós-colheita

Abstract: RESUMODoenças de pós-colheita podem trazer importantes prejuízos, pois causam deterioração do produto e inviabilizam a comercialização do mesmo, devido à redução da qualidade dos frutos. No mamão, essas perdas podem ocorrer principalmente durante o armazenamento. Dentre essas doenças, podemos citar podridões causadas por fungos do gênero Colletotrichum, Lasiodiplodia, Fusarium, Phoma, Rhizopus, entre outros. Desse modo, para o manejo dessas doenças em pós-colheita, muitos agrotóxicos são utilizados de maneira … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…However, there was a significant loss of fresh weight in the fruits over ten days of storage. Mafra et al (2020) found no significant difference in the analysis of pH, TA, SS, and firmness of 'Formosa' papaya pulp submitted to treatment with A. nodosum seaweed extract (80 mL L -1 ), potassium phosphite (50 mL L -1 ), and organomineral fertilizer (3 mL L -1 ). The organomineral fertilizer evaluated in the study had the same composition as the product used in this research.…”
Section: Effects Of the Alternative Products On The Physical-chemicalmentioning
confidence: 74%
See 1 more Smart Citation
“…However, there was a significant loss of fresh weight in the fruits over ten days of storage. Mafra et al (2020) found no significant difference in the analysis of pH, TA, SS, and firmness of 'Formosa' papaya pulp submitted to treatment with A. nodosum seaweed extract (80 mL L -1 ), potassium phosphite (50 mL L -1 ), and organomineral fertilizer (3 mL L -1 ). The organomineral fertilizer evaluated in the study had the same composition as the product used in this research.…”
Section: Effects Of the Alternative Products On The Physical-chemicalmentioning
confidence: 74%
“…The application of organomineral fertilizer (3 mL L -1 ) enabled a 52% reduction in disease Research, Society and Development, v. 9, n. 10, e9629109330, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.9330 incidence compared to that of the control over four days of fruit storage and a 50% reduction in disease severity after eight days of storage (Mafra et al, 2020).…”
Section: Evaluation Of the Alternative Products To Control Green Moldmentioning
confidence: 99%
“…Mafra et al (18) indicam que no processo natural de amadurecimento dos frutos, desencadeiam mudanças fisiológicas que promovem o amolecimento do tecido vegetal, tornando-o mais suscetível ao ataque de patógenos e ao desenvolvimento de doenças pós-colheita.…”
Section: Resultsunclassified